2019
DOI: 10.3389/fimmu.2019.01160
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Cells Mediate Immune Responses and Cross-Protection Against Influenza A Virus

Abstract: Intraperitoneal inoculation with live influenza A virus confers protection against intranasal infections in mice and ferrets. However, the responses of peritoneal cells to influenza A virus have not been investigated. Here we show that intraperitoneal inoculation with A/WSN/1933 (H1N1) virus induced virus-reactive IgG production in the peritoneal cavity in mice. The infection resulted in substantial but transient B cell and macrophage depletion along with massive neutrophil infiltration, but virus growth was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(48 citation statements)
references
References 58 publications
4
44
0
Order By: Relevance
“…Peritoneal cells, bone marrow cells, and splenocytes were harvested at 5, 7, and 14 days post-infection, and cell populations were analyzed by ow cytometry. In the wild type mice, depletion of CD19 + B cells was observed at 5 days post-infection in the peritoneal cavity (Figure 2a) and bone marrow (Figure 2b), followed by a partial recovery at 7 days and restoration to near-normal levels at 14 days post-infection as previously described [26]. In CD83 KO mice, transient depletion and then recovery to the normal level were observed in CD19 + B cells of the peritoneal cavity similar to wild type mice ( Fig.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Peritoneal cells, bone marrow cells, and splenocytes were harvested at 5, 7, and 14 days post-infection, and cell populations were analyzed by ow cytometry. In the wild type mice, depletion of CD19 + B cells was observed at 5 days post-infection in the peritoneal cavity (Figure 2a) and bone marrow (Figure 2b), followed by a partial recovery at 7 days and restoration to near-normal levels at 14 days post-infection as previously described [26]. In CD83 KO mice, transient depletion and then recovery to the normal level were observed in CD19 + B cells of the peritoneal cavity similar to wild type mice ( Fig.…”
Section: Resultssupporting
confidence: 80%
“…Although CD83 is a key component of the immune system that can modulate T cell and B cell function, no studies involving CD83 and in uenza virus have been carried out so far. Recently, we demonstrated that intraperitoneal injection of in uenza A/WSN/1933 virus induced an e cient immune response and robust virus-speci c antibody production by B cells that su ciently provides cross-protection against other strains of in uenza A virus [26]. Here, we investigated the effect of CD83 on B and T cells during in uenza virus infection using C57BL/6J wild type mice in parallel with CD83 KO mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BALB/c mice were intraperitoneally infected with different doses of H3N2 and the virus-reactive antibody production (IgG and IgM) was measured by ELISA 7 days post infection. The levels of influenza H3N2-reactive IgG and IgM increased in the peritoneal cavity fluids and sera in a dose-dependent manner ( Figures 1A-D), although the number of B cells in the peritoneal cavity and bone marrow decreased after infection with the highest dose (1 × 10 8 pfu) of the virus (Gautam et al, 2019). The amount of IgG3 was higher than those of other IgG classes, which is similar to the IgG repertoire after intraperitoneal infection with WSN (Gautam et al, 2019).…”
Section: Immune Responses To High-dose Intraperitoneal Influenza a Inmentioning
confidence: 98%
“…Intraperitoneal infection can make the abdominal and pelvic organs accessible to the pathogens because of the circulation of peritoneal fluid throughout the pelvis and abdomen (Pannu and Oliphant, 2015). In our previous study, high-dose [1 × 10 8 plaque forming units (pfu)] intraperitoneal infection of mice with influenza A/Hongkong/4801/2014 virus (H3N2) resulted in 50% mortality, whereas low-dose (5 × 10 6 pfu) intraperitoneal infection with influenza A A/WSN/1933 virus (WSN) induced production of IgG that was cross-reactive to other influenza A viruses, a substantial but transient depletion of B cells and macrophages, and massive neutrophil infiltration of the peritoneal cavity (Gautam et al, 2019).…”
Section: Introductionmentioning
confidence: 99%